Efektivitas Bimbingan untuk Calon Pengantin Dalam Mewujudkan Keluarga yang Sakinah di Kantor KUA Tembung Kecamatan Percut Sei Tuan - Nuh Ahmad Syarodzi Ritonga; Muhammad Darmawan Saputra; Noval Al Nafiz Siregar; Alwi Padly Harahap; Uqbatul Khair (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The realization of sakinah family in a marriage requires a sufficient knowledge and understanding of the marriage understanding for couples who will hold a marriage, because potential problems in the family or household at any time can arise and threaten the family integrity even resulting in divorce. Director General of Islamic Community Guidance, since 2009 has issued a Regulation on The Course of Brides-to-be due to consideration of increasing the number of disputes, divorces and domestic violence which are the contributing factors are the lack of knowledge and understanding of the bride and groom about the meaning of home and family life, as well as to realize the life of Sakinah, mawaddah and warrahmah family, also to minimize the number of divorce and domestic violence. In 2013 issued Regulation No. DJ- II/542 on Guidelines for The Implementation of Premarital Courses as the basis for the implementation of premarital guidance by subdistrict KUA. In this study, researcher formulated two research problems, namely how to implement the implementation of sakinah family guidance in Percut Sei Tuan Subdistrict KUA, and how effective is the guidance of the Sakinah family in KUA Percut Sei Tuan Subdistrict. Keywords: Implementation, Guidance and Sakinah Family